ANALISIS PENILAIAN KINERJA KEUANGAN DAERAH PADA PEMERINTAH DAERAH PROVINSI NUSA TENGGARA BARAT - Nasruddin; Nia Kurniati; Syaumudinsyah; Iswan (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2025)
Government financial statements are an important component of creating public sector accountability. The purpose of financial statements is to provide information used to evaluate managerial and organizational performance. To evaluate government financial performance, ratio analysis is used. This study aims 1) to analyze the assessment of regional financial performance related to regional financial capability, regional financial capability, and regional dependence on the center, 2) to analyze the ratio of revenue and expenditure growth, 3) to analyze the effectiveness of revenue and expenditure efficiency. This research method is a qualitative method, the data used is secondary data in the form of the NTB Regional Government Budget Realization Report for the period 2020-2023, then the data will be analyzed using financial ratio analysis. The results showed that the ratio of financial capability and independence has increased, and the dependency ratio has decreased, which means that the local government is able to carry out the authority of decentralization. The revenue growth ratio in 2020 and 2022 is negative, meaning that there is no increase in revenue, while in 2021 and 2023 it is positive, meaning that it has increased, but the average revenue effectiveness ratio is in the good enough category. In the ratio of expenditure growth ratio> 40% inefficient category. This is because government spending increases every year along with the increase in development and community services.